Does adjunctive hemoadsorption provide benefit in the management of ischemia–reperfusion syndrome following near-drowning? A case report - Kovacevic, Pedja; Dragic, Sasa; Jandric, Milka; Momcicevic, Danica; Malesevic, Vedrana; Kovacevic, Tijana; Matejic-Spasic, Marijana; Knezevic, Tanja; Zlojutro, Biljana (Frontiers in Medicine, 2024)
Drowning remains a significant global health concern, claiming over 300,000 lives annually, with a disproportionate impact on young individuals in low-and middle-income countries. Conventional mechanical ventilation, while common, falls short in addressing the hypoxemia and hypercapnia often observed in severe near-drowning cases. Veno-venous extracorporeal membrane oxygenation (vvECMO) emerges as a critical intervention for cardiopulmonary failure post-drowning. This case report delves into the pivotal role of ischemia-reperfusion injury (IRI) in a near-drowning-related pathology. Following the initial insult, reoxygenation exacerbates the inflammatory cascade, resulting in a surge of pro-inflammatory mediators. In this context, CytoSorb â , a hemoadsorption cartridge, demonstrates promise by effectively removing these mediators from circulation. This report outlines its application in a critically ill adolescent patient who experienced near-drowning, presenting a compelling case for CytoSorb as an adjunctive therapy in managing IRI-induced hyperinflammation.